DESAIN LKS BERBASIS VIRTUAL LABORATORY MELALUI ICT PADA MATERI TEKNOLOGI DIGITAL, EFEK COMPTON, DAN INTI ATOM KELAS XII SMA/MA - Yeni Mustika Sari; Yenni Darvina; Masril Masril; Hidayati Hidayati (Universitas Negeri Padang, 2018)
The purposes of this research are to produce a virtual laboratory based LKS through ICT on material there are digital technology, compton effect, and atomic nucleus by knowing the value of validity and practicality. Type of research used is Research and Development (R&D) using research step by Sugiyono with research steps that is first to know potency and problem, gather information, design product, validate design, improve design, test product, product revision, trial usage product, product manufacture. The object of this research is LKS based on virtual laboratory through ICT. Based on data analysis, there are three research results. First, the design of LKS based on virtual laboratory through ICT. Second, the average validity value of experts with a value of 89.79 with criteria is very valid. Third, the average value of practicality by teachers with a value of 87.22 with very practical criteria. It can be concluded that the LKS based on virtual laboratory through ICT is very valid and very practical for use in physics learning of SMA XII class.